STRATEGIC MARKETING ANALYSIS FOR CICI CATERING: A CASE STUDY IN MAMUJU DISTRICT - Muh. Sayuti Bahmid; Andi Indra Martini; Jamaludin Kamarudin (SEAN Institute, 2023)
The analysis of Cici Catering Food Stall in Mamuju Regency highlights its internal strengths, such as practical presentation of local delicacies, affordable pricing, and consistent flavors, balanced by weaknesses like limited promotion and variety. External opportunities include community favoritism, job creation, and partnerships, while threats encompass emerging competitors, price rivalry, and pandemic-related challenges. The IFAS and EFAS evaluations position the business in SWOT Quadrant 1, indicating a balanced alignment of strengths and opportunities. With a score of 0.74, the conclusion is that Cici Catering Food Stall is a growing enterprise, poised to capitalize on strengths, address weaknesses, seize opportunities, and navigate challenges. Emphasizing innovation, menu expansion, and quality customer experiences will likely drive its ongoing success.